Manajemen Keuangan Pada Usaha Mikro, Kecil Dan Menengah (UMKM): Studi Pada UMKM Perikanan Di Kecamatan XIII Koto Kampar - Ismon Zakya HS; Arbaini; Heryudarini Harahap; Herwanto (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2017)
Financial management is an activity of planning, budgeting, inspection, controlling, searching and deposit funds owned by the organization or company.This study aims was to assess the condition of financial management of fishery MSMEs and how government support to MSMEs fisheries in XIII Koto Kampar subdistrict. The study was conducted in XIII Koto Kampar Sub District. The subjects were 30 fishery MSMEs. The study method was cross-sectional. Data analysis was descriptive. The results showed that the current ratio of 18 (60%) business actors above 2.68, 12 (40%) of MSMEs did not have debt in running their business that means also have a current ratio above 150%. It was found 17 (57%) MSMEs that had a quick ratio 5 to 30 that was above the ideal value of 1.5. There was one MSMEs whose quick ratio is 1that meant illiquid. The solvency ratio (debt ratio) was 0.01 to 0.11. It was found 12 (40%) MSMEs has received support from the government in the form of buildings, fish processing tables and other facilities located in fisheries centers, and business accounting management training assistance.